Evaluasi Program Standar Kompetensi Lulusan Al Qur’an (SKL Al Qur’an) Di Jurusan Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah Dan Keguruan, IAIN Surakarta, Tahun 2017 - Subar Junanto (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2018)
Abstract: The purpose of this research is to evaluate SKL Alquran Program. This research used mixed method. The students of SKL Quran program are being subject of this study and the lecturers are being informants because they are also the examiner of SKL Quran. This study examines data collection derived from quitioners, intervies, observations, and documentations. It also examines data validity by using triangulation, which means analysis qualitatif using interactive analysis and quantitative using percentile formula. The results show that SKL Quran needs to be evaluated in the context as an important category. The inputs of charateristic form explain that most participants of SKL Quran come from public school education background. Evaluation process also shows that the things of SKL Quran are needed to be improved in the process such as subjectivity examiners that always have been affect to students graduation of SKL Quran. Last, evaluation of the product knowledge of this study is going to graduate 77.42%. Keywords: Evaluation, SKL quran, FITK IAIN Surakarta